2021
DOI: 10.1049/elp2.12026
|View full text |Cite
|
Sign up to set email alerts
|

Cogging torque reduction based on segmented skewing magnetic poles with different combinations of pole‐arc coefficients in surface‐mounted permanent magnet synchronous motors

Abstract: The calculation and reduction of cogging torque are fundamental to the evaluation and optimisation of motor performance. Considering that the accuracy of the cogging torque calculated by analytical method (AM) is low, an accurate calculation model of the effective air‐gap length considering the actual stator slot structure and suitable for any motor is proposed, the cogging torque of 6p36s surface‐mounted permanent magnet synchronous motor (SPMSM) are calculated accurately and verified by finite element method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Magnetic attraction results from a force component in the x direction and a force component in the y direction. The magnetic attraction force approaches zero, as inferred from Equation ( 16) and (17), where the forces F x and F y result in an asymmetrical shape.…”
Section: The Axial Force and Fault-tolerance Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…Magnetic attraction results from a force component in the x direction and a force component in the y direction. The magnetic attraction force approaches zero, as inferred from Equation ( 16) and (17), where the forces F x and F y result in an asymmetrical shape.…”
Section: The Axial Force and Fault-tolerance Analysismentioning
confidence: 85%
“…Dual side PM motors are troublesome due to their high cogging torque, even though they have higher flux density and torque than traditional single side PM motors. For AFFSPM machines, a number of techniques, including slots/poles skewing, magnet segmentation, and harmonic field current injection, have been proposed to reduce two unfavourable factors, including the cogging torque and torque ripple [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the comparison fairness, except for the difference in pole arc coefficient configuration and rotor assembly form, other machine configurations including amount of PMs are kept the same. It is worth noting that previous research work has shown that the 4-segment structure is a more reasonable choice for the machine with rotor segmented skew poles [23]. Therefore, 4-segment structure is adopted in the machine with rotor segmented skew poles in this study.…”
Section: Machine Comprehensive Performance Evaluationmentioning
confidence: 99%
“…In ref. [13], the rotor pole skewing is used to reduce the torque ripple, and influence of different skewing segment numbers on the torque ripple is researched. In ref.…”
Section: Introductionmentioning
confidence: 99%